Numerical Microstructure Prediction for Lattice Structures Manufactured by Electron Beam Powder Bed Fusion - Koepf, Johannes A.; Pistor, Julian; Markl, Matthias; Körner, Carolin (Crystals, 2024)
The latest advances in additive manufacturing have given rise to an increasing interest in additively built lattice structures due to their superior properties compared to foams and honeycombs. The foundation of these superior properties is a tailored microstructure, which is difficult to achieve in additive manufacturing because of the variety of process parameters influencing the quality of the final part. This work presents the numerical prediction of the resulting grain structure of a lattice structure additively built by electron beam powder bed fusion. A thermal finite-difference model is coupled to a sophisticated cellular automaton-based crystal growth model, including nucleation. Numerically predicted grain structures, considering different nucleation conditions, are compared with experimentally derived EBSD measurements. The comparison reveals that nucleation is important, especially in fine lattice structures. The developed software, utilizing the nucleation model, is finally able to predict the as-built grain structure in lattice structures.
CRIS-Team Scopus Importer:2024-03-08
Keywords: cellular automaton; finite difference; lattice structure; microstructure; nucleation; numerical simulation